Numerical Study on Combustion and Atomization Characteristics of Coaxial Injectors for LOX/Methane Engine - Jiabao Xu; Ping Jin; Ruizhi Li; Jue Wang; Guobiao Cai (International Journal of Aerospace Engineering)
The LOX/methane engine has an admirable performance under a supercritical state. However, the properties of methane change drastically with varying injection temperature. Because the injector can greatly affect the atomization and combustion, this study performed a three-dimensional numerical simulation of atomization, combustion, and heat transfer in a subscale LOX/methane engine to evaluate the effect of the main fluid parameters with different methane injection temperatures and different injectors on atomization performance and combustion performance. The results show that the larger propellant momentum ratio and Weber number can improve the heat flux and combustion stability in shear coaxial injector, while the influence in swirl coaxial injector is relatively small. Moreover, in shear coaxial injector and in swirl coaxial injector, the larger propellant momentum ratio and Weber number can reduce the droplet size, enhance atomization performance, and improve the combustion efficiency. The numerical model provides an economical method to evaluate the main fluid parameters and proposes new design principles of injectors in LOX/methane engine.